Income, economic efficiency and strategic analysis of smallholder buffalo farming in Biboki Anleu District - Josua Sahala; Marselinus Banu; Wolfhardus Vinansius Feka; Febrya Christin Handayani Buan; Achmad Nur Chamdi (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2026)
Smallholder buffalo farming plays an important role in supporting rural livelihoods in Biboki Anleu District, North Central Timor Regency, particularly as a source of household income, traditional asset, and socio-cultural exchange in local communities. This study aims to analyze farmers’ income, economic efficiency, factors affecting income, and strategic development of smallholder buffalo farming. A survey was conducted involving 37 buffalo farmers selected through a census approach. Data were analyzed using income analysis, Return Cost Ratio, multiple linear regression, and SWOT analysis. The results show that buffalo farming generated an average annual income of IDR 108,127,975.60 per farmer, with an R/C ratio of 5.754, indicating that the business is economically feasible and efficient. Feed cost and farming experience significantly influenced farmers’ income. The high efficiency was supported by the use of local feed resources and agricultural by-products, such as sago, rice straw, and kabesak leaves, which reduced cash production costs. The study concludes that smallholder buffalo farming has strong economic potential when supported by local resource-based feed management, improved market information, breeding services, and farmer training. Strategic development should prioritize feed processing, institutional support, and population sustainability.